1996
DOI: 10.1590/s0004-282x1996000100013
|View full text |Cite
|
Sign up to set email alerts
|

Meningite bacteriana neonatal: estudo prospectivo da evolução a longo prazo de 55 crianças

Abstract: RESUMO -Foram estudadas prospectivamente 55 crianças que apresentaram meningite bacteriana no período neonatal, com o objetivo da analisar a frequência e o tipo de sequelas neurológicas. Todas as crianças nasceram a termo, sendo 38 do sexo masculino e 17 do feminino; a idade de início da doença variou de 3 a 28 dias. Os principais agentes etiológicos foram as enterobactérias. O tempo médio de seguimento foi 5 anos. A frequência de sequelas neurológicas foi 67,3%, representadas principalmente pelo atraso do des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
1
6
1
3
Order By: Relevance
“…Despite the decrease in mortality rate compared to prior studies conducted at the same Service, which showed mortality rates of 29% 10 and 26% 12 , the complications affected 50% of the patients in both groups. Others authors have emphasized the high morbidity of neonatal bacterial meningitis [11][12][13] , regardless of the decrease in the mortality.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Despite the decrease in mortality rate compared to prior studies conducted at the same Service, which showed mortality rates of 29% 10 and 26% 12 , the complications affected 50% of the patients in both groups. Others authors have emphasized the high morbidity of neonatal bacterial meningitis [11][12][13] , regardless of the decrease in the mortality.…”
Section: Discussioncontrasting
confidence: 72%
“…The association between positive CSF culture and the presence of complications or death has been reported by other authors 9,12 . It is likely that the presence of bacteria or their products in the CSF is related to the maintenance of the infl ammatory cascade and central nervous system injury.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Este comportamento pode ser atribuído, em parte, ao grande número de recém-nascidos pré-termo acometidos, ao tempo transcorrido entre o início da doença e a introdução do tratamento, ao tipo de bactéria, à sensibilidade do microorganismo aos antimicrobianos e à capacidade do antibiótico atingir o sítio de infecção [4][5][6] . A mortalidade nos diferentes centros de tratamento varia de 17% a 29%, com taxa de seqüelas de 15% a 68% dos sobreviventes 3,[7][8][9][10] . Entre os fatores que influenciam o prognóstico da doença estão a prematuridade, o peso de nascimento, o tipo de bactéria, a sensibilidade do germe ao antimicrobiano, a duração do tratamento e a presença de complicações.…”
unclassified